(untitled) (Research, Society and Development, 2022)
Introduction: Obesity and NAFLD are diseases that have been growing proportionally, it is estimated that in the year 2025, about 700 million people will be affected by obesity, while 20% of the global population will contract hepatic steatosis. And, in both diseases, treatment occurs with lifestyle changes (diet, exercise, and especially weight loss), so the use of additional methods can increase the effectiveness of your treatment. Objectives: The objective of this study is to analyze the effects of using Uxi Amarelo (Endopleura Uchi) on the effectiveness of the treatment of non-alcoholic Fatty Liver Disease in obese people. Methodology: This is an exploratory research with a qualitative approach. Results and Discussion: Uxi Amarelo presents physicochemical characteristics with acidic pH, in relation to weight, it presents a significant difference in relation to the findings in the literature, since the edible part represents only 4.08% of the fruit. Regarding its nutritional composition, it is a fruit with high energy value, high lipid content and low protein content. In addition, its use in the treatment of NAFLD in animals was highly effective, as a substance called Bergenin is present, with hepatoprotective and antioxidant properties, which act on metabolic stress and decrease the amount of liver enzymes, thus contributing to the improvement of hepatocytes in NAFLD. Conclusion: Uxi Amarelo can be used as an additional method in the treatment of NAFLD, however, further studies must be carried out to understand its mechanism of action to improve hepatocytes.